HUBUNGAN KEBERSIHAN GIGI DAN MULUT,INDEKS PLAK DAN PH SALIVA TERHADAP KEJADIAN KARIES GIGI PADA ANAK DI BEBERAPA PANTI ASUHAN KOTA SEMARANG - Dhimas Adi Putranto; Henry Setiawan Susanto; Mateus Sakundarno Adi (Jurnal Kesehatan Masyarakat (Undip), 2020)
Abstract: Dental caries is a damage process of hard tooth enamel tissue. The process of dental caries results from long-term formation of dental plaque. The purpose of this study  to analyze the relationship of dental and oral hygiene, plaque index, salivary pH to the incidence of dental caries in children of several orphanages in Semarang City. This study uses a cross sectional study design. The research sample amounted to 85 samples with total sampling. The research used questionnaires instrument, examination equipment and dental examination sheets. The results of this study are there is a relationship between plaque index (p value 0.08), OHI-S status (p value 0.001), salivary pH (p value 0.01). And there is no relationship of age (p value 0.589), gender (p value 0.710). Based on the results of the study it is recommended that orphanages caregivers pay more attention to the dental hygiene of orphans children and teach them how to brush their teeth, children are advised to brush their teeth before going to sleep and check their teeth to the doctor at least once every 6 months.